Red Cell Distribution Width as a Predictor of Persistent Pulmonary Hypertension of the Newborn - Sagheb, Setareh; Sepidarkish, Mahdi; Mohseni, Sayyed Ourmazd; Movahedian, Amirhossein; Mosayebi, Ziba (American Journal of Perinatology, 2017)
Objective Persistent pulmonary hypertension of the newborn (PPHN) is a critical condition with high mortality and morbidity rates in neonatal intensive care unit (NICU) admitted neonates due to severe hypoxemia. The aim of this study was to evaluate red cell distribution width (RDW) as a biomarker of hypoxemia and determine the optimal cutoff point of RDW for identifying neonates with PPHN.Study Design All PPHN diagnosed, NICU admitted term infants with hypoxemia after birth from May 2014 to September 2016 were enrolled as case control and healthy term infants with nonhemolytic jaundice who were admitted for phototherapy on the second or third day of birth were the control group. Blood samples were collected. Multiple logistic regression modeling was used to examine the association between PPHN and RDW.Results Receiver-operating characteristics (ROC) curve analysis was used to determine the optimal cutoff point of RDW for identifying neonates with PPHN. RDW was higher in the PPHN group compared with the control group (p < 0.001). Significant predictors of PPHN were mother's underlying disease (p = 0.01) and RDW (p < 0.001). The optimal RDW cut point for prediction of PPHN by the ROC curve analysis was 17.9 (sensitivity = 85.71%). RDW's area under the curve was 0.9197 (p < 0.001).Conclusion RDW may be a simple, valuable, accessible marker for predicting PPHN before performing echocardiography in hypoxemic NICU admitted neonates.
Keywords: persistent pulmonary hypertension of the newborn; hypoxemia; neonatal intensive care unit; red cell distribution width